Comprehensiveness and usability of tools for assessment of energy saving measures in schools. (February 2013) - Smith, Greta Caruana; Mumovic, Dejan; Curtis, Lee
Having in mind constantly changing regulatory frameworks which demand both carbon emission reduction and improvement of the quality of internal environment, this paper analyses strengths and limitations of available design tools of various complexity: Annex 36 Energy Concept Advisor Tool and an approved Dynamic Simulation Model. As a platform for discussion, two representative school buildings in North London were selected and modelled using both tools. Discussion integrates views of 76 building industry professionals on applicability of various school retrofit options in practice. Using the available statistics on total number of schools and floor space in each category, a simple extrapolation was applied to roughly quantify potential for carbon emission reduction of the school building stock in England and Wales. Practical applications : More than 70% of approximately 25, 000 maintained and independent primary and secondary schools in England and Wales were built before the introduction of thermal regulations in 1970s, offering a significant opportunity to reduce carbon emission of the school building stock. In terms of construction, they could be divided in two major categories: pre 1919 solid wall construction and post war masonry cavity school buildings. This paper reviews capabilities of the less-known Energy Concept Advisor which offers designers, architects and decision makers the opportunity of assessing the performance of a particular building and comparing possible retrofitting measures quickly.